ANALISIS PENDAPATAN DAN KELAYAKAN USAHA KOPRA DI KELURAHAN LEMBOMAWO KECAMATAN POSO KOTA SELATAN KABUPATEN POSO - Rantjendo, Destin Rilda; Laapo, Alimudin; Sulaeman, Sulaeman (AGROTEKBIS, 2018)
This study aims to determine the income and feasibility in managing coconut into copra. This research has been conducted in Lembomawo village, South Poso City district of Poso regency. Determining the location of the research is done intentionally (Porposive) with the consideration that Lembomawo Village is one of coconut production center. The timing of the research starts from January to February 2017. The analysis used is income and Feasibility Analysis. The results showed that the average income earned by copra farmers was Rp 6,945,484/harvest season. The average variable cost used by copra farmers in their activities was Rp 1,110,890.32 / harvest season and fixed cost of Rp 45,616.62 The result of research indicates that the activity of copra business is Rp. 5,788,976.93 and the copra business feasibility indicates 5.78.